WASTE MANAGEMENT SYSTEM AND REVERSE LOGISTICS OF TEŠANJ - Galijašević, Emir; Nunić, Zdravko; Alihodžić, Asib (Horizons - International Scientific Journal, 2018)
The modern society is based on tested strategies in all spheres of its existence. We are living in a quite turbulent and rushing society. Those strategies are reflected in everything, among which we include the strategy of waste management systems which make the society profitable and sustainable. Talking and mentioning waste management is something relative new and it's got popular the last few years in our society on the Balkans. Adequate waste management represents one of the major challenges that all urban environments are facing. We have seen the results that the western countries have done on this field, so the focus now is on the Balkan countries. It is necessary to manage this system in a way that will provide additional values, enable selective separation and recycling. Unfortunately, in this region this is rare, or a small percentage of waste is recycled. Our region is heading towards the EU integration, and one of the field that must and needs to be improved is the field of environment. Therefore, the purpose of this research is to analyze the current situation in waste management systems and greenlogistics in the municipality of Tešanj. The municipality of Tešanj is one of the most developed municipalities in Bosnia and Herzegovina. More than 45 000 people are living on the territory of municipality of Tešanj, and more than 12 000 of them are working on the territory. The purpose of this work is to show how a small municipality in B&H is dealing with the waste management. The residents are part of the interest group, which in deed has a lot it's of influence on the efficiency of this system, so the emphasis in this research is precisely on that group. The age of the people who attended the survey was from the age of 15 to 60+. The process of gathering data was done selectively through a survey that was organized online. Some of the media sites from Tešanj gave their help to gather the data including one radio station. The analysis of the collected data confirmed that a large number of citizens take care of their waste, and have information how much it is important to take care about their waste. but also that there are certain problems which are reflected due to the absence of infrastructure, as well as the improvement of cooperation between the citizens and the utility company „RAD“ d.d. Tešanj with the municipality Tešanj as the local intermediator authority. The purpose at the end was to show how all residents in the municipality of Tešanj can and need to take care in their local community about the waste management, and if only one resident engage itself it can lead that more and more people engage, and in the end this leads to a safer and cleaner environment.